FAUNA DE COLEOPTERA MELOLONTHIDA E DE VILLA LAS ROSAS, CHIAPAS, MÉXICO - Alcázar Ruiz, José Antonio; Morón Ríos, Alejandro; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2003)
A study of the nocturnal Melolonthidae beetle fauna of Villa Las Rosas, Chiapas, México is presented. Data were obtained during 1999-2000 with 103 nights of collecting effort at lights near the borders of subdeciduos tropical forest and pine-oak forest, located at 1,240 m of altitude. Records of 3 subfamilies, 9 tribes and 50 species of the genera Diplotaxis, Phyllophaga, Polyphylla, Hoplia, A nomala, Pelidnota, Cyclocephala, Euetheola, Ligyrus, Coelosis, Enema, Strategus, Xyloryctes, Spodistes, A rchophileurus, Hemiphileurus and Phileurus are included. Higher specific diversity is presented in the genera Phyllophaga (16 spp.) and, A nomala (11 spp.). Phyllophaga tenuipilis (Bates), P. ravida (Blanchard), Xyloryctes lobicollis Bates and, A nomala inconstans Burmeister were the most abundant species in the samples. A rchophileurus simplex (Bates) and Phyllophaga anolaminata (Moser) are cited for firsttime in México, and A nomala decolor Bates, A . forreri (Bates), Diplotaxis consentanea Bates, D. simillima Moser and, Hoplia squamifera Burmeister are recorded for first time from Chiapas state. A key to the 50 species is included. Most genera represented in the study area have Neotropical origin, but 51 % of the species belong to Paleoamerican dispersal pattern (sensu Halffter 1976). The Melolonthidae fauna of Villa Las Rosas area is 27.72% similar (QS Sorensen) with the species found in Los Tuxtlas, Veracruz; and 27.40% similar with the species from the mountains at northeast of Hidalgo, Mexico.